2021
DOI: 10.13057/biodiv/d221012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dragon fruit (Selenicereus) species in Mekong Delta based on DNA barcode sequences

Abstract: Abstract. Huy TG, Men TT, Thi NPA, Khang DT. 2021. Identification of dragon fruit (Selenicereus) species in Mekong Delta based on DNA barcode sequences. Biodiversitas 22: 4216-4222. Selenicereus species is one of the valuable fruiting plants in Vietnam due to its properties, e.g., rich nutrition and medicine activity. Eight DNA barcodes applied to the discrimination power of dragon fruit species in the Mekong delta. Total DNA extracted from fresh roots and the loci of interest were amplified and sequenced. DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The sign "." exhibits nucleotide similar to that of the first sample; the sign "_" exhibits the missing nucleotide position; HC: Ha Chau cultivar, DD: Red cultivar, DX: Xiem cultivar, DXA: Green cultivar In comparison with previous studies in other land plants, rpoC1 gene showed highly conservative among closely related species in the genus Selenicereus (Huy et al 2021). Although rpoC1 gene exhibited 100% for amplification success, this plastid gene was not able to distinguish Dendrobium (Orchidaceae), indicated by the species resolution was only 38.89%, which was the lowest percentage among five tested markers including ITS, matK, rbcL, rpoB, and rpoC1 (Singh et al 2012).…”
Section: Rpoc1 Genementioning
confidence: 76%
“…The sign "." exhibits nucleotide similar to that of the first sample; the sign "_" exhibits the missing nucleotide position; HC: Ha Chau cultivar, DD: Red cultivar, DX: Xiem cultivar, DXA: Green cultivar In comparison with previous studies in other land plants, rpoC1 gene showed highly conservative among closely related species in the genus Selenicereus (Huy et al 2021). Although rpoC1 gene exhibited 100% for amplification success, this plastid gene was not able to distinguish Dendrobium (Orchidaceae), indicated by the species resolution was only 38.89%, which was the lowest percentage among five tested markers including ITS, matK, rbcL, rpoB, and rpoC1 (Singh et al 2012).…”
Section: Rpoc1 Genementioning
confidence: 76%
“…The cultivation and consumption of pitaya has increased dramatically in recent years due to its unique appearance and rich nutritional content [14]. Pitaya is reportedly grown mainly in the Americas, southern Mexico, Costa Rica, El Salvador, Venezuela, Colombia, Ecuador, Panama, Brazil, and Uruguay [15][16][17][18]. Pitaya grown in each region has different characteristics.…”
Section: About Pitayamentioning
confidence: 99%